2021
DOI: 10.1002/cctc.202002019
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Offset Deactivation Effect of Potassium and Phosphorus on MnEuOx SCR Catalyst

Abstract: In this study, a remarkable offset deactivation effect of K and P on MnEuOx SCR catalyst has been found. Experimental results showed that the NO conversion over K−P poisoned catalyst was close to 80 % at 250 °C. Several characterization techniques containing NH3‐TPD, XPS, H2‐TPR, XRD and in situ DRIFT were used to reveal the mechanism of the offset effect. The characterization of NH3‐TPD and H2‐TPR suggested that the introduction of P on MnEuOx‐K could improve its surface acidity and redox ability. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although SCR denitration technology based on vanadium-based catalysts has been widely applied and possesses good catalytic performance in high-temperature ranges, it still has many shortcomings such as the high conversion of SO 2 to SO 3 , formation of N 2 O at high temperature, poisoning deactivation by alkali metals in the fly ash, high toxicity of vanadium, and relatively expensive raw materials. , Therefore, developing alternative catalysts for commercial vanadium-based SCR catalysts is an important topic in this field. Mn-based catalysts, introduced in this section, have good activities in the low-temperature range (90–180 °C) and are environmentally friendly, which has obtained the widespread interest of scholars .…”
Section: Mechanism Of Alkali Metal Poisoning On Scr Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SCR denitration technology based on vanadium-based catalysts has been widely applied and possesses good catalytic performance in high-temperature ranges, it still has many shortcomings such as the high conversion of SO 2 to SO 3 , formation of N 2 O at high temperature, poisoning deactivation by alkali metals in the fly ash, high toxicity of vanadium, and relatively expensive raw materials. , Therefore, developing alternative catalysts for commercial vanadium-based SCR catalysts is an important topic in this field. Mn-based catalysts, introduced in this section, have good activities in the low-temperature range (90–180 °C) and are environmentally friendly, which has obtained the widespread interest of scholars .…”
Section: Mechanism Of Alkali Metal Poisoning On Scr Catalystmentioning
confidence: 99%
“…Their studies indicated that the changes of the AC (active carbon) structure and the reduction of surface chemisorbed oxygen, NH 3 , and NO adsorption, which resulted from the combined effect of KCl and As 2 O 3 , were responsible for the poisoning deactivation of the Mn–Ce/AC catalyst. Guo et al found a remarkable offset deactivation effect of K and P on the MnEuO x SCR catalyst. The research results showed that the NO conversion of the K–P poisoning catalyst was close to 80%, while the K poisoning catalyst was only 50%.…”
Section: Mechanism Of Alkali Metal Poisoning On Scr Catalystmentioning
confidence: 99%
“…The MCT catalyst and T 0.06 MCT catalyst have three peaks at 334.5 °C, 390 °C and 505.5 °C. These reduction peaks could be attributed to the continuous reduction process of MnO 2 →Mn 2 O 3 →Mn 3 O 4 →MnO [36]. The reduction peak of cerium oxide and thulium oxide could not be found because of the overlap with the reduction peak of manganese oxide [37].…”
Section: Reduction Property and Surface Aciditymentioning
confidence: 97%